A new phenolic glycoside from the Idesia polycarpa Maxim. leaves. Issue 20 (18th October 2019) - Huang, Lei; Peng, Tong; Li, Yu; He, Yunyun; Wang, Li; Zhang, Shiyan; Sun, Yiran; Chen, Fang; Tang, Lin
Abstract: Phytochemical investigation on the ethyl acetate extract of Idesia polycarpa Maxim. Leaves led to the isolation of four phenolic glycoside isomers (1–4 ). Compound2 appeared to be new reported phenolic glycoside, while compound1 was the first time isolated from the titled species. Their structures were established by IR, UV, HRESI-MS and 1D and 2D NMR spectroscopies analysis and comparison of spectral data with previously reported data. The compounds3 and4 showed stronger activity of scavenging the DPPH free radical than the other two compounds, while the compounds1 and2 showed a significant activity of scavenging the ABTS free radical. Compounds2 and4 exhibited stronger cytotoxicity against HepG2 cell lines compared to compounds1 and3 . Moreover, compound3 presented the highest cytotoxicity against MCF cell lines with IC50 value of 37.17 ± 0.26 μg/mL than compounds1, 2 and4 . Abstract :